2021
DOI: 10.1177/13591053211037730
|View full text |Cite
|
Sign up to set email alerts
|

The role of behavioural immune system and belief in COVID-19 misinformation on COVID-19 protective behaviours in Indonesia

Abstract: This study ( N = 1306) investigated the role behavioural immune system and specific beliefs in COVID-19 misinformation in predicting COVID-19 protective behaviours. By analysing the data from an online survey, we found that germ avoidance significantly predicted social distancing and was negatively correlated to transportation use. Belief in conspiracy theories and non-psychological cures and prevention methods were negatively associated to social distancing, while the latter also predicted lower preventive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…Furthermore, Covid Worry did not show an impact on Individual Choice. Our findings follow the trend of other studies in that they indicate that there was a link between reactions to Covid-19 and preventative behaviours such as social distancing [ 33 , 34 , 35 ] and positive attitudes towards public health policies ([ 52 ]).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Covid Worry did not show an impact on Individual Choice. Our findings follow the trend of other studies in that they indicate that there was a link between reactions to Covid-19 and preventative behaviours such as social distancing [ 33 , 34 , 35 ] and positive attitudes towards public health policies ([ 52 ]).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we interpret the results as indicating correlational relationships and use correlational language in our discussion. These methods are essentially regression based and are in line with other studies [ 33 ,[ 34 ] 34 ] on similar topics. Alpha was set at 0.05.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…In applying the PMT, it is probable that those with high levels of germ aversion appraise the threat associated with the pandemic as high and thus engage in more protective coping behaviors (e.g., strictly adhering to prevention protocols). For example, germ aversion has been shown to predict social distancing and reduced use of public transportation [ 72 ]. These strategies can prevent infection and consequently enhance feelings of safety and control, thereby fostering resilience.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that individual differences in the BIS were associated with transportation service use during the COVID-19 pandemic ( Prawira et al, 2021 ). Individuals with a more reactive BIS (i.e., germ aversion) reported less use of public transportation and app-based ridesharing services during the COVID-19 pandemic ( Prawira et al, 2021 ). This finding provides initial support that the BIS is associated with transportation service use during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%